Banking returns and monetary variables in periods of economic stability: Australian Evidence - Simpson, John; Evans, John (Taiwan Institute of Business Administration, 2007)
The purpose of this study is to examine dynamic interactions and long-term equilibrium relationships between banking stock returns and key monetary variables in a period of relative economic stability, post financial deregulation in Australia. The importance of the study lies in its demonstration of banking market efficiency under these environments supporting rational expectations in Australian banking. Vector autoregressive models are applied to analyse optimally lagged data. In a bivariate bank stock returns model which includes interest rates and exchange rates there is evidence of cointegration. Consistent with theory, Australia's bank stock returns and long-term interest rates are negatively related. Long-term interest rates are exogenous. The study is also important as it demonstrates that in these environments, interest rates and exchange rates assist in the forecasting of Australian bank returns. In accordance with theory, contractionary monetary policy implementation leads to lower banking stock returns and expansionary policy will have the opposite effect.